Reducing poverty through community empowerment with integrated coconut product program in Bujjulu District of Gowa Regency - Aslinda, Andi; Zainal, Henni; Siraj, Muhammad Luthfi (Linguistics and Culture Review, 2021)
Poverty is still an urgent agenda that needs to be addressed by the Government in Gowa Regency, especially the poor, to empower the people in the Bujjulu area. The purpose of the study was to analyze poverty reduction by community empowerment through integrated coconut products in Bujjulu District, Gowa Regency. The research method used is a qualitative approach. The data collection techniques used are observation methods, interview methods, and documentation methods. The data analysis technique in this study used are data condensation, data display (data presentation), conclusion drawing/verification The result of the research is that Bujjulu Village, Gowa Regency is mostly carried out with the principle of learning by doing so that this integrated coconut program can be expected to produce an increase in family income in particular. The implementation of this training focused on making flower pots from coconut fiber, making charcoal and briquettes as alternative fuels as a substitute for oil and gas which are currently difficult to obtain, making nata de coco, and transforming the coconut into copra.